Factors influencing the local cure rate of hidradenitis suppurativa following wide local excision. Issue 1 (3rd November 2019) - Ngaage, Ledibabari M.; Wu, Yinglun; Ge, Shealinna; Gebran, Selim; Liang, Fan; Rada, Erin M.; Nam, Arthur J.; Silverman, Ronald P.; Rasko, Yvonne M.
Abstract: Wide local excision is the gold standard and only potential curative therapy for recalcitrant hidradenitis suppurativa. However, high recurrence rates persist even post‐surgery with little known on the influencing factors for remission. We evaluated the effect of patient, disease, and operative factors on local cure rate of moderate to severe hidradenitis following wide local excision. We performed a retrospective chart review for all patients who had undergone surgical excision of hidradenitis at a university hospital from 2012 to 2018. We identified 79 patients with a total of 220 operative sites. The majority were obese (mean body mass index [BMI] 32.5), female (71%), African‐American (84%), and had a mean age of 31 years. A quarter of operative sites experienced a recurrence (n = 56). Patients who achieved remission had a significantly lower number of affected regions than those who experienced a recurrence (2.3 vs 3.6, P = .0023). Additionally, recurrence rate differed significantly between body locations ( P = .0440). Smoking, BMI, Hurley grade, closure method, and excision size did not influence local cure rate. Surgical excision remains a worthy management option for hidradenitis patients with three quarters achieving remission after a single operation. Number of affected regions and location of hidradenitis may play a factor in recurrence.